Exposure to non‐ionizing electromagnetic radiation of public risk prevention instruments threatens the quality of spermatozoids. Issue 2 (29th September 2018) - Tirpak, Filip; Slanina, Tomas; Tomka, Marian; Zidek, Radoslav; Halo, Marko; Ivanic, Peter; Gren, Agnieszka; Formicki, Grzegorz; Stachanczyk, Katarzyna; Lukac, Norbert; Massanyi, Peter
Contents: The use of artificial insemination in cattle breeding has evolved to global extent, and insemination doses are often shipped via air transport which requires strict radiation‐based examinations. For the determination of effect of non‐ionizing radiation (NIR), to which are beings frequently exposed due to protection of airport or cultural event security, freshly ejaculated and cryopreserved bovine spermatozoa were used as experimental model. Following radiation with hand‐held metal detector in various exposition times (0, 10 s, 15, 30 and 60 min—groups FR, FR10, FR15, FR30 and FR60) the spermatozoa underwent motility and DNA fragmentation analyses. Study on cryoconserved semen treated with NIR was performed in time intervals 0, 10 s, 1 and 5 min (insemination doses radiated before cryoconservation—CB, CB10, CB1, CB5; samples radiated after freezing—CA, CA10, CA1 and CA5). Fresh semen and insemination doses radiated after cryoconservation showed significantly lower total and progressive motility. No effect on motility parameters was detected in semen extended with cryopreservative medium and radiated prior to freezing. Surprisingly, NIR showed a potential to stimulate spermatozoa velocity; however, the effect was modulated throughout the post‐thawing incubation. Based on the DNA fragmentation assay, sperm DNA stayed intact. Present study underlines the potential harm of NIR, which is frequently used in everyday life, with overall adverse impact on human and animal reproduction. Current study also points out on interesting short‐term spermatozoa stimulation induced by NIR.